2016
DOI: 10.4049/jimmunol.1501840
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Activity Is Essential for ATP-Driven Unconventional Vesicle-Mediated Protein Secretion and Inflammasome Activation in Human Macrophages

Abstract: Extracellular ATP is an endogenous danger signal that is known to activate inflammatory responses in innate immune cells, including macrophages. Activated macrophages start to secrete proteins to induce an immune response, as well as to recruit other immune cells to the site of infection and tissue damage. In this study, we characterized the secretome (i.e., the global pattern of secreted proteins) of ATP-stimulated human macrophages. We show that ATP stimulation activates robust vesicle-mediated unconventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 68 publications
4
42
0
Order By: Relevance
“…Curiously, EGTA treatment increased full-length vimentin levels in cell extracts at 4 h; this observation was repeated several times. Furthermore, consistent with reports that Ng-induced inflammasome formation is independent of extracellular calcium (33) or calpain activity (34), neither EGTA nor MDL28170 prevented pyroptotic permeabilization or inflammasome formation (SI Appendix, Fig. S6).…”
Section: Resultssupporting
confidence: 90%
“…Curiously, EGTA treatment increased full-length vimentin levels in cell extracts at 4 h; this observation was repeated several times. Furthermore, consistent with reports that Ng-induced inflammasome formation is independent of extracellular calcium (33) or calpain activity (34), neither EGTA nor MDL28170 prevented pyroptotic permeabilization or inflammasome formation (SI Appendix, Fig. S6).…”
Section: Resultssupporting
confidence: 90%
“…Recent system level characterizations using modern mass spectrometrybased proteomics approaches have provided important novel information how innate immune cells, including macrophages, activate much more global protein secretion than just secreting cytokines and chemokines and that this global protein secretion is an important part of the innate immune response to different activation stimuli. We have previously shown that activators of canonical NLRP3 inflammasome, including monosodium urate and ATP, induce robust unconventional vesicle-mediated protein secretion in human macrophages (19,20). Our present results show that also non-canonical caspase-4/5 inflammasome activates EV-mediated protein secretion in human macrophages.…”
Section: Caspase-4/5 Inflammasome-activated Protein Secretionsupporting
confidence: 70%
“…Our present results show that also non-canonical caspase-4/5 inflammasome activates EV-mediated protein secretion in human macrophages. In addition, both canonical and non-canonical inflammasomes activated the secretion of many danger signal proteins (Table I) (19,20).…”
Section: Caspase-4/5 Inflammasome-activated Protein Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes have been proposed to mediate one of the mechanisms involved in the stimulation of P2X purinoceptor 7 receptor (P2X7R) that rapidly triggers a key step of the inflammatory response: the induction of NLRP3/caspase-1 inflammasome signalling complexes that drive the proteolytic maturation and secretion of the pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18) (6). ATP stimulation through a P2X7R-dependent pathway activates robust vesicle-mediated unconventional protein secretion, including exosome release and membrane shedding, and drives NLRP3 inflammasome activation in a calpain activity dependent manner (7). Also related, central nervous system trauma induces inflammasome activation and secretion of exosomes containing inflammasome protein cargo into cerebral spinal fluid that fuse with target cells to activate the innate immune response in peripheral tissues (8).…”
mentioning
confidence: 99%